No longer human - Dazai, Osamu (Singapore : Tuttle Publishing, 2023)
No Longer Human is the story of Yozo Oba, who, from early childhood, finds it impossible to form meaningful relationships with family or friends. As a child he copes by acting the fool$1 (Bmocking himself while entertaining others. As an adult he turns to alcohol, sex and drugs, which lead to his eventual self-destruction. Originally written in 1948 and based closely on Dazai's own life, the timeless and universal themes of social alienation, failure and one man's inner torture at his inability to feel like a normal human still resonate with young people everywhere, making this an enduring international classic.s
Keywords: YOUNG ADULT -- FICTION